Mitochondrial DNA abnormalities provide mechanistic insight and predict reactive oxygen species-stimulating drug efficacy - Tarek Zaidieh (BMC Cancer, 2021)
Abstract Background Associations between mitochondrial genetic abnormalities (variations and copy number, i.e. mtDNAcn, change) and elevated ROS have been reported in cancer compared to normal cells. Since excessive levels of ROS can trigger apoptosis, treating cancer cells with ROS-stimulating agents may enhance their death. This study aimed to investigate the link between baseline ROS levels and mitochondrial genetic abnormalities, and how mtDNA abnormalities might be used to predict cancer cells’ response to ROS-stimulating therapy. Methods Intracellular and mitochondrial specific-ROS levels were measured using the DCFDA and MitoSOX probes, respectively, in four cancer and one non-cancerous cell lines. Cells were treated with ROS-stimulating agents (cisplatin and dequalinium) and the IC50s were determined using the MTS assay. Sanger sequencing and qPCR were conducted to screen the complete mitochondrial genome for variations and to relatively quantify mtDNAcn, respectively. Non-synonymous variations were subjected to 3-dimensional (3D) protein structural mapping and analysis. Results Our data revealed novel significant associations between the total number of variations in the mitochondrial respiratory chain (MRC) complex I and III genes, mtDNAcn, ROS levels, and ROS-associated drug response. Furthermore, functional variations in complexes I/III correlated significantly and positively with mtDNAcn, ROS levels and drug resistance, indicating they might mechanistically influence these parameters in cancer cells. Conclusions Our findings suggest that mtDNAcn and complexes I/III functional variations have the potential to be efficient biomarkers to predict ROS-stimulating therapy efficacy in the future.